2019
DOI: 10.1186/s13075-019-1990-z
|View full text |Cite
|
Sign up to set email alerts
|

JAG2/Notch2 inhibits intervertebral disc degeneration by modulating cell proliferation, apoptosis, and extracellular matrix

Abstract: Background Intervertebral disc degeneration (IVDD)-related disorders are the major causes of low back pain. A previous study suggested that Notch activation serves as a protective mechanism and is a part of the compensatory response that maintains the necessary resident nucleus pulposus (NP) cell proliferation to replace lost or non-functional cells. However, the exact mechanism remains to be determined. In this study, we aimed to investigate the role of JAG2/Notch2 in NP cell proliferation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…As transmembrane receptors with a direct route from the membrane to the nucleus, Notch 1-4 can only exhibit such diverse functionality by a range of regulatory mechanisms such as tissue topology, ligand expression patterns, expression of certain enzymes, or the extent of cell–cell contact [ 234 ]. In IVD cells, the expression of Notch 2 is increased during DD [ 235 ], whereas intradiscal injection of JAG2 (which induces Notch 2) reduced DD processes in rats [ 236 ]. Notch signaling in the IVD was activated by hypoxia [ 237 ] and pro-inflammatory cytokine exposure [ 235 ], thereby activating NP and AF cell proliferation [ 236 , 237 ], inhibiting NP cell apoptosis promoted by TNF-α [ 236 ] and modulating the expression of anabolic and catabolic genes [ 238 ].…”
Section: Ivd Cell Activity and Molecular Biology In Health And Dismentioning
confidence: 99%
See 2 more Smart Citations
“…As transmembrane receptors with a direct route from the membrane to the nucleus, Notch 1-4 can only exhibit such diverse functionality by a range of regulatory mechanisms such as tissue topology, ligand expression patterns, expression of certain enzymes, or the extent of cell–cell contact [ 234 ]. In IVD cells, the expression of Notch 2 is increased during DD [ 235 ], whereas intradiscal injection of JAG2 (which induces Notch 2) reduced DD processes in rats [ 236 ]. Notch signaling in the IVD was activated by hypoxia [ 237 ] and pro-inflammatory cytokine exposure [ 235 ], thereby activating NP and AF cell proliferation [ 236 , 237 ], inhibiting NP cell apoptosis promoted by TNF-α [ 236 ] and modulating the expression of anabolic and catabolic genes [ 238 ].…”
Section: Ivd Cell Activity and Molecular Biology In Health And Dismentioning
confidence: 99%
“…In IVD cells, the expression of Notch 2 is increased during DD [ 235 ], whereas intradiscal injection of JAG2 (which induces Notch 2) reduced DD processes in rats [ 236 ]. Notch signaling in the IVD was activated by hypoxia [ 237 ] and pro-inflammatory cytokine exposure [ 235 ], thereby activating NP and AF cell proliferation [ 236 , 237 ], inhibiting NP cell apoptosis promoted by TNF-α [ 236 ] and modulating the expression of anabolic and catabolic genes [ 238 ]. Yet, these effects seem to be zone-dependent, with Notch activation causing catabolic and anabolic responses in AF and NP cells, respectively [ 238 ].…”
Section: Ivd Cell Activity and Molecular Biology In Health And Dismentioning
confidence: 99%
See 1 more Smart Citation
“…Low back pain (LBP) is one of the most common health problems, influencing the quality of people's life, and leading to huge global economic burden. 1,2 Evidence has been shown that intervertebral disc degeneration (IVDD) is a primary mechanical cause of LBP. 3 In addition, IVDD is characterized by decreased extracellular matrix (ECM), increased cell death and fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Additionally, it has been shown that multiple factors can induce the apoptosis of NP cells including infection, genetics, inflammatory cytokines, and signaling networks. 1,9 Recently, cell, growth factor, and gene therapy are the main therapies for the treatment of IVDD; 10 however, current strategies for the treatment of IVDD remains unsatisfying. Therefore, development of effective strategies for the patients with IVDD is extremely required.…”
Section: Introductionmentioning
confidence: 99%